Bronius Pranskus-Žalionis - kritikas, mokslininkas, pedagogas - Lisenkaitė, Liudvika (Literatūra, 1973)
The article is devoted to one of the first Lithuanian Marxist literary researchers, a well-known critic and historian of literature, Professor B. Pranskus-Žalionis. The author of the article shows in detail the years of studies of B. Pranskus at the Moscow State University (1923-1926) and at the Institute of Linguistic and Literary Research (1926-1929), emphasizes his educational and scientific contacts with V. Friche, investigates the formation of his literary-aesthetic views and the confirmation of these views in his practical activity. While describing the critical legacy of B. Pranskus, the author pays special attention to the articles, which were published in the Lithuanian communist press in 1920-1938. B. Pranskus’ works of literary research are classified according to their character and problems dealt with. Attempt is made to determine the contribution of the scientist to the solution of some particular problems. His pedagogical activity at the Lithuanian department of the Communist University of Western national minorities (1923-1936) and at the Vilnius State University (1958-64) is also described in the article. Some considerations of the author are based on the facts and material that have been unknown hitherto.